Rational Drivers and the Choice Between Congestion Tolls and Tradeable Permits: A Political Economy Model - Bruno L. De Borger; Amihai Glazer; Stef Proost (Center for Economic Studies and Ifo Institute (CESifo), 2021)
People who anticipate the introduction of a policy can adapt their behavior, perhaps in ways that make the policy ineffective and exacerbate the problem to be addressed. This paper develops a political economy model to study strategic behavior related to the introduction of congestion policies, focusing on tradeable driving permits and congestion tolls. We have the following results. First, anticipatory behavior after the policies are announced but prior to their introduction may make both congestion policies welfare-reducing. Second, drivers will oppose the policies even when they receive all permits for free, or toll revenues are distributed to drivers only. As a consequence, strategic behavior makes it more difficult to get a political majority to support both congestion policies. Third, in an infinite horizon setting, tradable permits are superior to congestion tolls in that they avoid strategic behavior once the system is implemented. In contrast, with congestion tolls the steady-state equilibrium implies continuing strategic behavior. Drivers will always strictly prefer a permit system over congestion tolls as long as they receive a sufficient share of the permits for free.
Keywords: H23; R41; R48; P16; 330; anticipatory behaviour; political economy; congestion tolls; tradeable driving permits; strategic behavior